Sie sind auf Seite 1von 8

MATH298 Set 14 2008/02/20

TAYLOR SERIES
The rst derivative and
the linear approximation
Denition of an ordinary derivative:
df(x)
dx
lim
h0
f(x +h) f(x)
h
If h is small but nite then
df(x)
dx

f(x +h) f(x)

h
or
f(x +h) f(x) +h
df
dx
(x)
Problem: how to obtain better approxima-
tions, by using not only linear but also higher
order terms in h?
1
Power series for a given function
Problem: nd a
j
so that around a given x,
f(x +h) = a
0
+a
1
h +a
2
h
2
+a
3
h
3
+a
4
h
4
. . .
Solution:
0) Substitute h = 0 in this equation, to nd that
a
0
= f(x).
1) Dierentiate the equation by h,
(f(x +h))
h
=
df
dx

(x+h)
1 = a
1
+2a
2
h+3a
3
h
2
+4a
4
h
3
+. . .
and substitute h = 0:
a
1
=
df
dx
(x)
2) Do it again and again,

2
f
h
2
(x +h) = 2a
2
+3 2a
3
h +4 3a
4
h
2
+. . .
2 a
2
=
d
2
f
dx
2
(x)

3
f
h
3
(x +h) = 3 2a
3
+4 3 2h +. . .
3 2 a
3
=
d
3
f
dx
3
(x)
. . .
2
Taylor series in one variable
f(x+h) = f(x)+h
df
dx
(x)+
h
2
2!
d
2
f
dx
2
(x)+ +
h
n
n!
d
n
f
dx
n
(x)+. . .
In dierent notations:
f(x) = f(a) +(x a)
df
dx
(a) +
(x a)
2
2!
d
2
f
dx
2
(a) +. . .
+
(x a)
n
n!
d
n
f
dx
n
(a) +. . .
Case of a = 0: Maclaurins seris
f(x) = f(0)+x
df
dx
(0)+
x
2
2!
d
2
f
dx
2
(0)+ +
x
n
n!
d
n
f
dx
n
(0)+. . .
3
Example 1
Obtain approximation of degrees up to 3 for the function
f(x) = e
x
2
Solution: Calculating the derivatives and substituting
x = 1, we get
f(x) = e
x
2
; f(1) = e
1
f

(x) = 2xe
x
2
; f

(1) = 2e
1
f

(x) = (4x
2
2)e
x
2
; f

(1) = 2e
1
f

(x) = (8x
3
+12x)e
x
2
; f

(1) = 4e
1
Then the Taylor series is
f(1 +h) = f(1) +f

(1)h +
1
2
f

(1)h
2
+
1
6
f

(1)h
3
+. . .
= e
1
_
1 2h +h
2
+
2
3
h
3
+. . .
_
or
f(x) = e
1
_
1 2(x 1) +(x 1)
2
+
2
3
(x 1)
3
+. . .
_
4
Example 1: illustration
Constant Linear
a
0
a
0
+a
1
h
0
1
0 1 2
x
f
0
1
0 1 2
x
f
a
0
+a
1
h +a
2
h
2
a
0
+a
1
h +a
2
h
2
+a
3
h
3
0
1
0 1 2
x
f
0
1
0 1 2
x
f
5
Taylor series in two variables:
derivation
Let us nd an approximation for the function f(x, y) at a
point (x
0
+h, y
0
+k) in terms of its properties at (x
0
, y
0
).
To do that, consider x and y depending on parameter
p, so that
x = x(p) = x
0
+hp, y = y(p) = y
0
+kp.
Thus we have u(p) = f(x(p), y(p)), and
f(x
0
, y
0
) = u(0), f(x
0
+h, y
0
+k) = u(1)
The value of u(1) can be approximated through prop-
erties of u at p = 0 using the Taylor (Maclaurin) series,
u(1) = u(0) +1
du
dp
(0) +
1
2
2
d
2
u
dp
2
(0)
+
1
n
n!
d
n
u
dp
n
(0) +. . .
The last formula (*) from Set 13 gives the expression
of the derivatives of u by p in terms of partial derivatives
of f by x and y:
d
n
u
dp
n
=
_
h

x
+k

y
_
n
f.
Thus we obtain . . .
6
Taylors formula for two
independent variables
f(x
0
+h, y
0
+k) = f(x
0
, y
0
)
+
_
hf

x
(x
0
, y
0
) +kf

y
(x
0
, y
0
)
_
+
1
2!
_
h
2
f

xx
+2hkf

xy
+k
2
f

yy
_
+
1
3!
_
h
3
f

xxx
+3h
2
kf

xxy
+3hk
2
f

xyy
+k
3
f

yyy
_
+. . .
1
n!
_
h

x
+k

y
_
n
f +. . .
(all partial derivatives are evaluated at point
(x
0
, y
0
))
7
Example 2
Derive the quadratic approximation for function f(x, y) = sinxy
0
, y
0
) = (1, /3).
Solution
f(x, y) = sin(1 /3), f(x
0
, y
0
) =

3/2;
f
x
(x, y) = y cos xy, f
x
(x
0
, y
0
) = /6;
f
y
(x, y) = xcos xy, f
y
(x
0
, y
0
) = 1/2;
f
xx
(x, y) = y
2
sinxy, f
xx
(x
0
, y
0
) =
2

3/18;
f
xy
(x, y) = xy sinxy +cos xy, f
xy
(x
0
, y
0
) =

3/6 +1/2;
f
yy
(x, y) = x
2
sinxy, f
yy
(x
0
, y
0
) =

3/2
Substituting these results in formula of Taylors expansion of
f(x, y), we obtain
sinxy

3
2
+
_

6
(x 1) +
1
2
_
y

3
__
+
1
2!
_

3
18
(x 1)
2
+2
_

3
6
+
1
2
_
(x 1)
_
y

3
_

3
2
_
y

3
_
2
_
.
8